Two-layer tube and production method of the same
A two-layer tube with specific inner and outer layer compositions and properties effectively addresses hydrochloric acid permeation and cracking issues, ensuring long-term chemical containment and equipment safety in semiconductor manufacturing.
Patent Information
- Application Number
- JP2024095161
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-13
- Filing Date
- 2024-06-12
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2044-06-12
AI Technical Summary
Conventional fluorine-containing resin tubes used for transporting chemical solutions like hydrochloric acid face issues with hydrochloric acid permeation and cracking when exposed to hot water for extended periods, leading to equipment corrosion and environmental pollution.
A two-layer tube design with an inner layer containing tetrafluoroethylene and perfluoro(propyl vinyl ether) units and an outer layer of chlorotrifluoroethylene, optimized for low hydrochloric acid permeability and resistance to cracking, achieved by controlling the weight loss rate, thickness ratio, and zero shear viscosity of the inner layer.
The two-layer tube maintains low hydrochloric acid permeability and prevents cracking even in hot water for long durations, reducing the frequency of replacements and ensuring chemical integrity in semiconductor manufacturing.
Smart Images

Figure 2024178935000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a dual-wall tube and a method for producing the same. [Background technology]
[0002] Patent Document 1 describes a chlorotrifluoroethylene copolymer-containing laminate having a layer (A) made of a tetrafluoroethylene / perfluorovinyl ether copolymer and / or a tetrafluoroethylene / hexafluoropropylene copolymer and a layer (B) made of a chlorotrifluoroethylene copolymer, characterized in that the layer (A) and the layer (B) are laminated by co-extrusion molding under conditions in which the flow path temperature before contact between the material (a) of the layer (A) and the material (b) of the layer (B) in a multi-layer die is 300 to 400°C for the flow path (pa) through which the material (a) flows and 250 to 350°C for the flow path (pb) through which the material (b) flows. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2006 / 095857 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present disclosure is to provide a double-walled tube that maintains low hydrochloric acid permeability even when left in warm water for a long period of time with an aqueous hydrochloric acid solution sealed therein. [Means for solving the problem]
[0005] According to the present disclosure, there is provided a two-layer tube comprising an inner layer (A) and an outer layer (B) provided directly on the inner layer (A), wherein the inner layer (A) contains a copolymer (a) containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, and the outer layer (B) contains a polymer (b) containing at least chlorotrifluoroethylene units, wherein the weight loss rate of the copolymer (a) after heat treatment at 380°C for 1 hour is 0.05 mass% or less, and the ratio of the thickness of the inner layer (A) to the thickness of the outer layer (B) ((A) / (B)) is 30.0 / 70.0 to 67.0 / 33.0. Effect of the Invention
[0006] According to the present disclosure, it is possible to provide a double-walled tube that maintains low hydrochloric acid permeability even when the tube is left in warm water for a long period of time with an aqueous hydrochloric acid solution sealed therein. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional image of the tube produced in Comparative Example 1. [Diagram 2] FIG. 2 is a cross-sectional image of the tube produced in Comparative Example 2. [Diagram 3] FIG. 3 is a cross-sectional image of the tube produced in Example 1. [Figure 4] FIG. 4 is a schematic diagram of an experimental apparatus used for measuring the permeability coefficient of 35% by mass hydrochloric acid through a double-walled tube. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.
[0009] The present disclosure relates to a dual-layer tube comprising an inner layer (A) and an outer layer (B).
[0010] Patent Document 1 describes that conventionally, fluororesin tubes such as PFA resin tubes have been widely used to transport chemical liquids such as hydrochloric acid, hydrofluoric acid, nitric acid, etc., which are used in semiconductor and liquid crystal factories; however, the permeation of the chemical liquid from the tube causes the tube itself to whiten and deteriorate, increasing the acid concentration in the factory, causing problems such as corrosion of equipment and environmental pollution, and that in order to improve this, it is desirable to have tubes with a small chemical liquid permeation coefficient.
[0011] Patent Document 1 describes that when layer (A) is formed using a tetrafluoroethylene / perfluorovinyl ether copolymer and / or a tetrafluoroethylene / hexafluoropropylene copolymer, layer (B) is formed using a chlorotrifluoroethylene copolymer, and layer (A) and layer (B) are laminated by coextrusion molding under conditions of a flow path temperature within a specific range described below, the resulting laminate has a small 35% by mass hydrochloric acid permeability coefficient at 25°C.
[0012] However, it has now become clear that while conventional tubes are difficult to pass through hydrochloric acid in low-temperature water, cracks will appear in the inner layer if the tubes are left in warm water for long periods of time, and that the tubes are unable to sufficiently inhibit the passage of hydrochloric acid if the tubes are left in room-temperature water for long periods of time.
[0013] Therefore, after intensively studying the means for solving this problem, it was found that by forming the inner layer of the bilayer tube from a copolymer containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, and by appropriately adjusting the weight loss rate after heat treatment at 380°C for 1 hour, and further by adjusting the thickness of the inner layer and the outer layer within a very limited range, a bilayer tube can be obtained that is unlikely to crack in the inner layer even when left in hot water for a long period of time with hydrochloric acid aqueous solution sealed therein, and that can maintain low hydrochloric acid permeability even when left in water at room temperature for a long period of time.The bilayer tube of the present disclosure has been completed based on this finding.
[0014] Next, the configuration of the double-layer tube of the present disclosure will be described in more detail.
[0015] The two-layer tube of the present disclosure comprises an inner layer (A) and an outer layer (B), the inner layer (A) containing a copolymer (a) containing tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units, and the outer layer (B) containing a polymer (b) containing at least chlorotrifluoroethylene (CTFE) units.
[0016] <Inner layer (A)> The inner layer (A) contains a copolymer (a) containing TFE units and PPVE units. The copolymer (a) has a specific weight reduction rate.
[0017] The weight loss rate of the copolymer (a) is 0.05% by mass or less, and preferably 0.01% by mass or more.
[0018] The weight loss rate of the copolymer (a) can be reduced to 0.05% by mass or less by subjecting the copolymer (a) to an appropriate heat treatment, as described below.
[0019] The weight loss rate of the copolymer (a) can be calculated from the weight of the copolymer (a) before and after heat treatment at 380° C. for 1 hour according to the following formula. Weight reduction rate (mass%) = [(weight before heating) - (weight after heating)] / (weight before heating) x 100
[0020] It is presumed that the copolymer with a low weight loss rate after heat treatment at 380°C for 1 hour contains almost no high-temperature volatile matter with a molecular weight of 3000 or less. The high-temperature volatile matter with a molecular weight of 3000 or less may exist in an amorphous state in a molded product of the crystalline copolymer (a) and form a fine amorphous and low-density phase. The hydrochloric acid flowing inside the two-walled tube may be retained in this phase, and the heat of association between the acid molecules and the water molecules may cause thermal expansion stress, which may cause cracks to occur, or may cause the permeation of hydrochloric acid to be insufficiently suppressed even if cracks do not occur. It is presumed that by forming the inner layer (A) from the copolymer (a) with a weight loss rate of 0.05 mass% or less, the formation of an amorphous and low-density phase is suppressed, the generation of fine cracks that may occur in the inner layer (A) is suppressed, and the excellent low hydrochloric acid permeability of the two-walled tube is maintained.
[0021] The zero shear viscosity of the copolymer (a) is preferably 2.00×10 because it is possible to further suppress the occurrence of cracks in the inner layer and to further suppress the permeation of hydrochloric acid while maintaining good moldability of the copolymer (a). 4 Pa·S or more, more preferably 2.50×10 4 Pa·S or more, and more preferably 3.00×10 4 Pa·S or more, preferably 10.00×10 4 Pa·S or less, and more preferably 8.00×10 4 Pa·S or less, and more preferably 5.00×10 4 It is below Pa·S.
[0022] The zero shear viscosity of the copolymer (a) can be adjusted by adjusting the melt flow rate and the content of the PPVE unit of the copolymer (a), as well as by adjusting the amount of the polymerization initiator, the amount of the chain transfer agent, the polymerization pressure, the polymerization time, etc., when producing the copolymer (a).
[0023] The zero shear viscosity of copolymer (a) is the viscosity at a frequency of 0.1 rad / sec at 340° C. in the melt viscoelasticity measurement of copolymer (a). The zero shear viscosity can be measured using a melt viscoelasticity measuring device.
[0024] The MIT value of the copolymer (a) is preferably 2.6 million or more, more preferably 10 million or less, and even more preferably 5 million or less, since the occurrence of cracks in the inner layer can be further suppressed and the permeation of hydrochloric acid can be further suppressed.
[0025] The MIT value of the copolymer (a) can be adjusted by adjusting the melt flow rate and the content of the PPVE unit of the copolymer (a).
[0026] The MIT value of the copolymer (a) can be determined by compression molding the copolymer (a) to prepare a test piece having a width of 12.7 mm, a length of 90 mm, and a thickness of 0.20 to 0.25 mm, bending the test piece under conditions of a load of 1.25 kg, a bending angle of 135 degrees on the left and right, and a bending frequency of 175 times / min, and measuring the number of times (MIT value) until the test piece breaks.
[0027] The copolymer (a) contains TFE units and PPVE units.
[0028] The content of the PPVE units in the copolymer (a) is preferably 4.0 to 6.5 mass%, more preferably 4.5 mass% or more, even more preferably 5.0 mass% or more, and particularly preferably 5.5 mass% or more, based on the total monomer units, since this can further suppress the occurrence of cracks in the inner layer and further suppress the permeation of hydrochloric acid.
[0029] The content of TFE units in copolymer (a) is preferably 93.5 to 96.0 mass% based on all monomer units, more preferably 95.5 mass% or less, even more preferably 95.0 mass% or less, and particularly preferably 94.5 mass% or less.
[0030] The copolymer (a) may contain monomer units derived from a monomer copolymerizable with TFE and PPVE.
[0031] Monomers that can be copolymerized with TFE and PPVE include hexafluoropropylene (HFP), CZ 3 Z 4 =CZ 5 (CF2) n Z 6 (In the formula, Z 3 , Z 4 and Z 5 are the same or different and represent H or F; Z 6 represents H, F or Cl, and n represents an integer of 2 to 10. 7 (In the formula, Rf 7 represents a perfluoroalkyl group having 1 to 5 carbon atoms.) Among these, HFP is preferred.
[0032] The content of monomer units derived from monomers copolymerizable with TFE and PPVE is preferably 0 to 1.5% by mass, more preferably 0.5% by mass or less, and further preferably 0.1% by mass or less.
[0033] As the copolymer (a), at least one selected from the group consisting of copolymers consisting of only TFE units and PPVE units, and TFE / HFP / PPVE copolymers is preferred, since this can further suppress the occurrence of cracks in the inner layer and further suppress the permeation of hydrochloric acid, and a copolymer consisting of only TFE units and PPVE units is more preferred.
[0034] In the present disclosure, the content of each monomer unit in the copolymer is 19 Measured by F-NMR.
[0035] The melting point of the copolymer (a) is preferably 295 to 308° C., since this can further suppress the occurrence of cracks in the inner layer and can further suppress the permeation of hydrochloric acid.
[0036] In the present disclosure, the melting point of the copolymer (a) is the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10° C. / min (second run) using a differential scanning calorimeter (DSC).
[0037] The copolymer (a) is preferably a fluororesin having melt processability. In the present disclosure, melt processability means that the polymer can be melted and processed using conventional processing equipment such as an extruder and an injection molding machine. Therefore, the melt processable fluororesin usually has a melt flow rate of 0.01 to 500 g / 10 min, as measured by the measurement method described below.
[0038] The melt flow rate (MFR) of the copolymer (a) is preferably 10.0 g / 10 min or less, more preferably 5.0 g / 10 min or less, even more preferably 3.0 g / 10 min or less, and is preferably 0.01 g / 10 min or more, more preferably 0.1 g / 10 min or more, and even more preferably 1.0 g / 10 min or more, because this can further suppress the occurrence of cracks in the inner layer and further suppress the permeation of hydrochloric acid.
[0039] The MFR of the copolymer (a) is measured in accordance with ASTM D1238 using a die having a diameter of 2.1 mm and a length of 8 mm, under a load of 5 kg and at 372°C.
[0040] The number of functional groups of the copolymer (a) is 10 carbon atoms. 6 There may be 500 or less per molecule, preferably 300 or less, more preferably 200 or less, even more preferably 100 or less, still more preferably 50 or less, and particularly preferably 10 or less.
[0041] The functional group is a functional group present at the end of the main chain or the end of the side chain of the copolymer, and a functional group present in the main chain or the side chain. The functional group is preferably at least one selected from the group consisting of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH.
[0042] The type of functional group and the number of functional groups can be identified by infrared spectroscopy.
[0043] Specifically, the number of functional groups is measured by the following method. First, the copolymer is melted at 340 to 350°C for 30 minutes and compression molded to prepare a film with a thickness of 0.05 to 0.25 mm. This film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the copolymer, and a difference spectrum with a base spectrum that is completely fluorinated and has no functional groups is obtained. From the absorption peaks of specific functional groups that appear in this difference spectrum, the number of carbon atoms in the copolymer is calculated according to the following formula (A): 6 Calculate the number of functional groups per unit, N. N=I×K / t (A) I: Absorbance K: Correction coefficient t: film thickness (mm)
[0044] For reference, the absorption frequencies, molar absorption coefficients, and correction coefficients for the functional groups in this disclosure are shown in Table 1. The molar absorption coefficients were determined from FT-IR measurement data of low molecular weight model compounds.
[0045] [Table 1]
[0046] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are shown in the table. The absorption frequencies of -CF2H, -COF, -COOH free, -COOH bonded, -COOCH3, and -CONH2 are several tens of Kaiser (cm -1) lower. Therefore, for example, the functional group number of -COF is the absorption frequency of 1883 cm due to -CF2COF. -1 The number of functional groups determined from the absorption peak of -CH2COF and the absorption frequency of 1840 cm -1 The number of functional groups is the sum of the number of functional groups determined from the absorption peaks of
[0047] The number of functional groups may be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH.
[0048] A functional group is introduced into a copolymer by, for example, a chain transfer agent or a polymerization initiator used in producing the copolymer. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain end of the copolymer. Also, a functional group is introduced into the side chain end of the copolymer by polymerizing a monomer having a functional group.
[0049] By subjecting a copolymer having such a functional group to a fluorination treatment, a copolymer having a number of functional groups within the above-mentioned range can be obtained. That is, the copolymer (a) may be one that has been fluorination-treated. The copolymer (a) may also have a -CF3 terminal group.
[0050] The inner layer (A) may contain various additives, such as a conductive filler, a stabilizer such as a heat stabilizer, a reinforcing agent, a bulking agent, an ultraviolet absorber, and a pigment, within the scope of the present disclosure.
[0051] <Outer layer (B)> The outer layer (B) contains a polymer (b) containing at least a CTFE unit.
[0052] As the polymer (b), at least one selected from the group consisting of polychlorotrifluoroethylene [PCTFE] and CTFE copolymer is preferred, since it can further suppress the occurrence of cracks in the inner layer and further suppress the permeation of hydrochloric acid, at least one selected from the group consisting of PCTFE, CTFE / TFE copolymer, and ethylene / CTFE copolymer is more preferred, and CTFE / TFE copolymer is even more preferred.
[0053] The polymer (b) is preferably a CTFE copolymer. The CTFE copolymer is preferably a copolymer having a CTFE unit and a copolymer of TFE, HFP, PAVE, vinylidene fluoride (VdF), vinyl fluoride, hexafluoroisobutene, or the formula: CH2=CX. 1 (CF2) n X 2 (In the formula, X 1 is H, F, or X 2 is H, F or Cl, and n is an integer of 1 to 10), and a unit derived from at least one monomer selected from the group consisting of ethylene, propylene, 1-butene, 2-butene, vinyl chloride and vinylidene chloride.
[0054] The CTFE copolymer is more preferably at least one selected from the group consisting of ethylene / CTFE copolymers and copolymers containing CTFE units and units derived from at least one monomer selected from the group consisting of TFE, HFP, and PAVE.
[0055] The ethylene / CTFE copolymer (ECTFE) is a copolymer containing ethylene units and CTFE units, and preferably contains 46 to 52 mol% of ethylene units and 54 to 48 mol% of CTFE units relative to the total of the ethylene units and CTFE units. ECTFE may be a binary copolymer consisting of only ethylene units and CTFE units, or may further contain polymerization units based on a monomer copolymerizable with ethylene and CTFE (for example, a perfluoro(alkyl vinyl ether) (PAVE) derivative).
[0056] The content of polymerized units based on monomers copolymerizable with ethylene and CTFE is preferably 0.01 to 5 mol % based on the total of ethylene units, CTFE units, and polymerized units based on the above-mentioned copolymerizable monomers.
[0057] The MFR of ECTFE is preferably 0.01 to 100 g / 10 min. The MFR of ECTFE is measured at a temperature of 230° C. and a load of 2.16 kg.
[0058] As the polymer (b), one containing a CTFE unit, a TFE unit, and a monomer (α) unit derived from a monomer (α) copolymerizable therewith is particularly preferred, since the occurrence of cracks in the inner layer can be further suppressed and the permeation of hydrochloric acid can be further suppressed.
[0059] The monomer (α) is not particularly limited as long as it is a monomer copolymerizable with CTFE and TFE, and examples thereof include ethylene, VdF, CF2=CF-ORf 1 (In the formula, Rf 1 Perfluoro(alkyl vinyl ether) (PAVE) represented by a perfluoroalkyl group having 1 to 8 carbon atoms, CX 3 X 4 =CX 5 (CF2) n X 6 (In the formula, X 3 , X 4 and X 5 are the same or different and are a hydrogen atom or a fluorine atom; X 6 is a hydrogen atom, a fluorine atom, or a chlorine atom; n is an integer of 1 to 10), 2 (In the formula, Rf 2 and alkyl perfluorovinyl ether derivatives represented by the formula (I) (a perfluoroalkyl group having 1 to 5 carbon atoms), among which at least one selected from the group consisting of PAVE, the vinyl monomers and alkyl perfluorovinyl ether derivatives is preferred, at least one selected from the group consisting of PAVE and HFP is more preferred, and PAVE is even more preferred.
[0060] For PAVE, CF2=CF-ORf 3 (In the formula, Rf 3 represents a perfluoroalkyl group having 1 to 5 carbon atoms.) is preferred, and examples thereof include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], perfluoro(propyl vinyl ether) [PPVE], perfluoro(butyl vinyl ether), and the like. Among these, at least one selected from the group consisting of PMVE, PEVE, and PPVE is more preferred, and PPVE is even more preferred.
[0061] As the alkyl perfluorovinyl ether derivative, Rf 2 is preferably a perfluoroalkyl group having 1 to 3 carbon atoms, and CF2=CF-OCH2-CF2CF3 is more preferable.
[0062] The ratio of CTFE units to TFE units in the polymer (b) is preferably 15 to 90 mol % of CTFE units and 85 to 10 mol % of TFE units, more preferably 20 to 90 mol % of CTFE units and 80 to 10 mol % of TFE units. Also preferred is a copolymer composed of 15 to 25 mol % of CTFE units and 85 to 75 mol % of TFE units.
[0063] The polymer (b) preferably contains 90 to 99.9 mol% of CTFE units and TFE units in total, and 0.1 to 10 mol% of monomer (α) units. If the monomer (α) units are less than 0.1 mol%, the moldability, environmental stress cracking resistance, and fuel cracking resistance tend to be poor, whereas if they exceed 10 mol%, the fuel barrier properties, heat resistance, and mechanical properties tend to be poor.
[0064] As the polymer (b), a CTFE / TFE / PAVE copolymer is particularly preferred since it can further suppress the occurrence of cracks in the inner layer and further suppress the permeation of hydrochloric acid.
[0065] In the CTFE / TFE / PAVE copolymer, the above-mentioned PAVE may be perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], perfluoro(propyl vinyl ether) [PPVE], perfluoro(butyl vinyl ether), etc., and among these, at least one selected from the group consisting of PMVE, PEVE and PPVE is preferred, with PPVE being more preferred.
[0066] In the CTFE / TFE / PAVE copolymer, the PAVE unit is preferably 0.5 mol % or more and preferably 5 mol % or less of the total monomer units. The content ratio (mol %) of each monomer in the CTFE / TFE / PAVE copolymer is preferably (15.0-24.9) / (75.0-84.9) / (0.1-10.0), more preferably (15.0-24.9) / (75.0-84.9) / (0.1-3.0).
[0067] The melting point of the polymer (b) is not particularly limited, but is preferably 160 to 270°C.
[0068] The melting point of the polymer (b) is the temperature corresponding to the maximum value on the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter (DSC).
[0069] The polymer (b) is preferably a fluororesin having melt processability. The MFR of the polymer (b) is preferably 0.5 to 100 g / 10 min, more preferably 1 g / 10 min or more, even more preferably 2 g / 10 min or more, more preferably 50 g / 10 min or less, and even more preferably 40 g / 10 min or less.
[0070] The MFR of the polymer (b) is measured in accordance with ASTM D1238 using a die having a diameter of 2.1 mm and a length of 8 mm, under a load of 5 kg, at any temperature within the general molding temperature range of fluoropolymers, about 230 to 350°C (for example, 297°C). The measurement temperature for the MFR of the CTFE / TFE / PAVE copolymer is 297°C.
[0071] The outer layer (B) may contain various additives, such as a conductive filler, a stabilizer such as a heat stabilizer, a reinforcing agent, a bulking agent, an ultraviolet absorber, and a pigment, within the scope of the present disclosure.
[0072] <Tube layer structure> The two-layer tube of the present disclosure comprises an inner layer (A) and an outer layer (B), and the outer layer (B) is directly bonded onto the inner layer (A). In the two-layer tube of the present disclosure, the boundaries between the adjacent layers do not necessarily need to be clear, and the molecular chains of the polymers constituting the layers may interpenetrate each other from the contact surfaces, resulting in a layer structure with a concentration gradient.
[0073] In the two-layer tube of the present disclosure, the ratio ((A) / (B)) of the thickness of the inner layer (A) to the thickness of the outer layer (B) is 30.0 / 70.0 to 67.0 / 33.0. If the ratio ((A) / (B)) is too small, when the tube is left in hot water for a long period of time with an aqueous hydrochloric acid solution enclosed therein, cracks are likely to occur in the inner layer, and low hydrochloric acid permeability cannot be maintained. If the ratio ((A) / (B)) is too large, permeation of hydrochloric acid cannot be sufficiently suppressed.
[0074] The ratio ((A) / (B)) of the thickness of the inner layer (A) to the thickness of the outer layer (B) is preferably 50.0 / 50.0 or more, and more preferably 60.0 / 40.0 or more, since this can further suppress the occurrence of cracks in the inner layer and further suppress the permeation of hydrochloric acid. In addition, a larger ratio ((A) / (B)) is advantageous in that it makes it easier to weld the two-layer tube of the present disclosure to other members such as joints, and also in that the mechanical strength of the welded portion is increased.
[0075] The thickness of the bilayer tube of the present disclosure, i.e., the total thickness of the inner layer (A) and the outer layer (B), is preferably 1.3 mm or more, more preferably 1.5 mm or more, preferably 10.0 mm or less, more preferably 5.0 mm or less, and even more preferably 2.0 mm or less. The thickness of the bilayer tube of the present disclosure may be about 1.6 mm (e.g., 1.56 to 1.64 mm). The bilayer tube of the present disclosure may be a 3 / 4 inch tube or a 1 / 2 inch tube.
[0076] The bilayer tube of the present disclosure according to one embodiment is characterized in that, after an acid aqueous solution containing at least one acid selected from the group consisting of hydrochloric acid, hydrofluoric acid, nitric acid, and sulfuric acid is sealed in the bilayer tube and left at room temperature for 150 days or more, no cracks having a length of 10 μm or more are present in the inner layer (A). The presence or absence of cracks can be confirmed by observing the cross section of the bilayer tube using a microscope.
[0077] The two-walled tube of the present disclosure according to one embodiment is characterized in that there are no cracks having a length of 10 μm or more in the inner layer (A) after 35% by mass hydrochloric acid is enclosed and left for 90 hours in warm water at 80° C. The presence or absence of cracks can be confirmed by observing the cross section of the two-walled tube using a microscope.
[0078] The bilayer tube of the present disclosure can be produced, for example, by a production method in which copolymer (a) is subjected to a heat treatment by blowing hot air at 200 to 280°C for 6 hours or more, and then the resulting copolymer (a) and polymer (b) are laminated to obtain a bilayer tube.
[0079] The temperature of the hot air is preferably 230° C. or higher, more preferably 250° C. or higher, and preferably 270° C. or lower, more preferably 260° C. or lower. If the temperature of the hot air is too low, high-temperature volatile matter cannot be sufficiently removed from the copolymer (a). If the temperature of the hot air is too high, the copolymer (a) may fuse to form lumps, or, when pellets of the copolymer (a) are used for the heat treatment, the pellets may be deformed.
[0080] The time for blowing hot air is 6 hours or more, preferably 8 hours or more, preferably 30 hours or less, more preferably 20 hours or less, and further preferably 15 hours or less. By continuously blowing hot air, it is possible to promote the removal of high-temperature volatile matter from the copolymer (a). When molding the copolymer (a), the copolymer (a) is heated and melted, but the short heating time during molding cannot sufficiently remove the high-temperature volatile matter from the copolymer (a).
[0081] The hot air that has come into contact with the copolymer (a) may contain high-temperature volatile matter. In order to promote the removal of high-temperature volatile matter from the copolymer (a), it is preferable to blow hot air onto the copolymer (a) while discharging a part or all of the hot air that has come into contact with the copolymer (a). If the hot air blown onto the copolymer (a) is circulated and blown onto the copolymer (a) again, or if the copolymer (a) is brought into contact with high-temperature gas in a closed system, the removal of high-temperature volatile matter may not proceed, and the weight loss rate of the copolymer (a) may not be adjusted to the above-mentioned range.
[0082] As a method for treating copolymer (a), a fluorination treatment for reducing the number of functional groups of copolymer (a) is known. Since the fluorination treatment is carried out by contacting copolymer (a) with a highly reactive fluorinating agent in a sealed container, the weight loss rate of copolymer (a) cannot be adjusted to within the above range even if the fluorination treatment is carried out at high temperature for a long time.
[0083] The hot air may be heated air, heated inert gas, etc. The stronger the hot air is blown, the more the removal of high-temperature volatile matter from the copolymer (a) can be promoted, but the blowing volume must be such that the copolymer (a) does not fly up.
[0084] The shape of the copolymer (a) to which the hot air is blown is not particularly limited, and may be a powder, pellets, etc. If the copolymer (a) is in the form of a powder, it is more likely to be blown up by the hot air, so the copolymer (a) is preferably in the form of pellets.
[0085] The method for laminating the copolymer (a) and the polymer (b) includes the following: A method in which the copolymer (a) and the polymer (b) are co-extruded to thermally bond the layers together (by melt adhesion); A method in which a layer containing copolymer (a) and a layer containing polymer (b) are separately prepared by an extruder, and the layers are then superimposed and bonded to each other by heat fusion; A method of preparing a monolayer tube containing a copolymer (a) and extruding a polymer (b) onto the surface of the monolayer tube using an extruder; A method in which a single-wall tube containing copolymer (a) is prepared, polymer (b) is electrostatically coated on the surface of the single-wall tube, and the resultant coated article is heated overall or from the coated side to heat and melt polymer (b). etc.
[0086] The coextrusion molding may be carried out by known multi-layer coextrusion methods such as a multi-manifold method and a feed block method.
[0087] The two-layer tube of the present disclosure can be suitably used as a tube for piping a chemical liquid for distributing the chemical liquid, and can be particularly suitably used as a tube for piping a chemical liquid used for transporting a high-purity chemical liquid for manufacturing semiconductor devices. The two-layer tube of the present disclosure is less susceptible to cracks in the inner layer and can maintain low chemical liquid permeability for a long period of time, so that it can be replaced less frequently than conventional two-layer tubes.
[0088] The two-wall tube of the present disclosure is preferably a tube for piping a chemical liquid for passing the chemical liquid. The above-mentioned chemical liquid includes chemical liquids used in semiconductor manufacturing, such as ammonia water, ozone water, hydrogen peroxide water, hydrochloric acid, sulfuric acid, resist liquid, thinner liquid, and developing solution. The above-mentioned chemical liquid is preferably an acid aqueous solution containing at least one acid selected from the group consisting of hydrochloric acid, hydrofluoric acid, nitric acid, and sulfuric acid. The two-wall tube of the present disclosure can suppress the permeation of the acid in such an acid aqueous solution for a long period of time.
[0089] The double-walled tube of the present disclosure can be used, for example, as a tube for use in semiconductor manufacturing facilities or semiconductor manufacturing equipment, such as a chemical liquid supply line for semiconductor manufacturing, a chemical liquid supply facility for semiconductor manufacturing, a semiconductor cleaning device, or a coater developer.
[0090] It is also preferable to use the two-layer tube of the present disclosure in a low humidity environment. By using the two-layer tube in a low humidity environment, the occurrence of cracks in the inner layer can be further suppressed, and the permeation of hydrochloric acid can be further suppressed. The humidity of the usage environment is preferably 60% or less, and more preferably 30% or less.
[0091] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.
[0092] <1> According to a first aspect of the present disclosure, The present invention provides a two-layer tube comprising an inner layer (A) and an outer layer (B) provided directly on the inner layer (A), wherein the inner layer (A) contains a copolymer (a) containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, and the outer layer (B) contains a polymer (b) containing at least chlorotrifluoroethylene units, wherein the weight loss rate of the copolymer (a) after heat treatment at 380°C for 1 hour is 0.05 mass% or less, and the ratio of the thickness of the inner layer (A) to the thickness of the outer layer (B) ((A) / (B)) is 30.0 / 70.0 to 67.0 / 33.0. <2> According to a second aspect of the present disclosure, The double-layer tube according to the first aspect is provided, in which the total thickness of the inner layer (A) and the outer layer (B) is 1.3 mm or more. <3> According to a third aspect of the present disclosure, There is provided a double-layer tube according to the first or second aspect, in which the total thickness of the inner layer (A) and the outer layer (B) is 1.6 mm. <4> According to a fourth aspect of the present disclosure, There is provided a double-walled tube according to any one of the first to third aspects, wherein the content of perfluoro(propyl vinyl ether) units in copolymer (a) is 4.0 to 6.5 mass % based on the total monomer units constituting copolymer (a). <5> According to a fifth aspect of the present disclosure, In the double-layer tube according to any one of the first to fourth aspects, the melting point of the copolymer (a) is 295 to 308°C. <6> According to a sixth aspect of the present disclosure, There is provided a double-layer tube according to any one of the first to fifth aspects, wherein the polymer (b) is a copolymer containing chlorotrifluoroethylene units, tetrafluoroethylene units and monomer (α) units derived from a monomer (α) copolymerizable therewith. <7> According to a seventh aspect of the present disclosure, According to any one of the first to sixth aspects, there is provided a double-walled tube, wherein the polymer (b) is a copolymer containing chlorotrifluoroethylene units, tetrafluoroethylene units and perfluoro(alkyl vinyl ether) units. <8> According to an eighth aspect of the present disclosure, The zero shear viscosity of copolymer (a) is 2.00 × 10 4 There is provided a double-walled tube according to any one of the first to seventh aspects, having a modulus of at least Pa·S. <9> According to a ninth aspect of the present disclosure, There is provided a double-layer tube according to any one of the first to eighth aspects, in which the MIT value of the copolymer (a) is 2.6 million times or more. <10> According to a tenth aspect of the present disclosure, There is provided a two-layer tube according to any one of the first to ninth aspects, in which an acid aqueous solution containing at least one acid selected from the group consisting of hydrochloric acid, hydrofluoric acid, nitric acid, and sulfuric acid is sealed inside and allowed to stand at room temperature for 150 days or more, after which no cracks having a length of 10 μm or more are present in the inner layer (A). <11> According to an eleventh aspect of the present disclosure, There is provided a two-layer tube according to any one of the first to tenth aspects, in which after 35% by mass of hydrochloric acid is enclosed and left in warm water at 80°C for 90 hours, no cracks having a length of 10 µm or more are present in the inner layer (A). <12> According to a twelfth aspect of the present disclosure, the copolymer (a) contains tetrafluoroethylene units, perfluoro(propyl vinyl ether) units, and other monomer units derived from monomers copolymerizable with tetrafluoroethylene and perfluoro(propyl vinyl ether), the content of perfluoro(propyl vinyl ether) units in the copolymer (a) is 4.0 to 6.5 mass% based on all monomer units constituting the copolymer (a), the content of tetrafluoroethylene units in the copolymer (a) is 93.5 to 96.0 mass% based on all monomer units constituting the copolymer (a), and the content of other monomer units in the copolymer (a) is 0 to 1.5 mass% based on all monomer units constituting the copolymer (a); The polymer (b) is a copolymer containing chlorotrifluoroethylene units, tetrafluoroethylene units and perfluoro(alkyl vinyl ether) units, and the content ratio of each monomer (chlorotrifluoroethylene units / tetrafluoroethylene units / perfluoro(alkyl vinyl ether) units (mol %)) is (15.0 to 24.9) / (75.0 to 84.9) / (0.1 to 10.0); The total thickness of the inner layer (A) and the outer layer (B) is 1.56 to 1.64 mm; The ratio ((A) / (B)) of the thickness of the inner layer (A) to the thickness of the outer layer (B) is 60.0 / 40.0 to 67.0 / 33.0. According to any one of the first to eleventh aspects, there is provided a double-layer tube. <13> According to a thirteenth aspect of the present disclosure, A method for producing a double-layer tube according to any one of the first to twelfth aspects, The present invention provides a method for producing a two-layer tube by performing a heat treatment on copolymer (a) by blowing hot air at 200 to 280°C for 6 hours or more, and then laminating the resulting copolymer (a) and polymer (b). EXAMPLES
[0093] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.
[0094] The values in the examples were measured by the following methods.
[0095] (Polymer Composition) 19 The measurements were performed using F-NMR.
[0096] (Melt Flow Rate (MFR)) According to ASTM D1238, the mass (g / 10 min) of the copolymer flowing out per 10 min from a nozzle with an inner diameter of 2.1 mm and a length of 8 mm was determined using a melt indexer (manufactured by Yasuda Seiki Seisakusho) at 372°C or 297°C under a load of 5 kg.
[0097] (Weight reduction rate) The aluminum cup was heated at 380°C for 30 minutes to remove volatile matter from the aluminum cup. Approximately 10 g of copolymer pellets were placed in the aluminum cup, and the aluminum cup containing the pellets was precisely weighed. The aluminum cup containing the pellets was heated at 380°C for 60 minutes. After heating, the aluminum cup containing the pellets was precisely weighed. The weight loss rate of the copolymer was calculated based on the following formula. Weight reduction rate (mass%) = [(weight before heating) - (weight after heating)] / (weight before heating) x 100
[0098] (Zero Shear Viscosity) The zero-shear viscosity of the copolymer was measured using a parallel plate attached as a measuring tool to an Anton Paar melt viscoelasticity measuring device MCR-302. The measurement temperature was 340°C, and the sample thickness was 1 mm. The frequency was swept from high to low, and the viscosity at a frequency of 0.1 rad / sec was taken as the zero-shear viscosity.
[0099] (MIT value) The MIT value of the copolymer was measured in accordance with ASTM D2176. Specifically, the copolymer was compression molded to prepare a test piece with a width of 12.7 mm, a length of 90 mm, and a thickness of 0.20 to 0.25 mm, which was then attached to an MIT testing machine (model number 12176, manufactured by Yasuda Seiki Seisakusho Co., Ltd.) and the test piece was bent under the conditions of a load of 1.25 kg, a bending angle of 135 degrees on the left and right sides, and a number of bending times of 175 times / min, to measure the number of times (MIT value) until the test piece broke.
[0100] (Melting Point) The melting points (2nd run) of the copolymers (a1) and (a2) were determined as the temperatures corresponding to the maximum values in the heat of fusion curves when the temperature was increased at a rate of 10°C / min (second run) using a differential scanning calorimeter (DSC). The melting point of the polymer (b1) was determined as the temperature corresponding to the maximum value in the heat of fusion curve when the temperature was raised at a rate of 10° C. / min using a differential scanning calorimeter (DSC).
[0101] In the examples and comparative examples, the following materials were used.
[0102] Copolymer (a1) TFE / PPVE copolymer TFE / PPVE (mass ratio): 96.5 / 3.5 MFR(372℃, 5kg):2.0g / 10min Weight loss rate after heat treatment at 380°C for 1 hour: 0.25% by mass Zero shear viscosity (340℃): 2.85×10 4 Pa·S MIT value: 800,000 times Melting point: 308℃
[0103] copolymer (a2) TFE / PPVE copolymer TFE / PPVE (mass ratio): 94.0 / 6.0 MFR(372℃, 5kg): 1.6g / 10min Weight loss rate after heat treatment at 380°C for 1 hour: 0.05% by mass Zero shear viscosity (340℃): 3.32×10 4Pa·S MIT value: 2.6 million times Melting point: 300℃
[0104] The weight loss rate of the copolymer (a2) was adjusted by the following method. 1 to 3 kg of pellets of the TFE / PPVE copolymer having the above-mentioned composition and MFR were spread on a tray, and the tray was placed in a hot air circulation type electric furnace. While heating the inside of the hot air circulation type electric furnace to a temperature of 250°C, hot air was passed through the heating furnace, and the pellets on the tray were heat-treated for 10 hours. In order to smoothly remove high-temperature volatile matter from the pellets, the heat treatment was performed while a part of the hot air that had passed through the heating furnace was exhausted to the outside of the heating furnace.
[0105] Polymer (b1) TFE / CTFE / PPVE copolymer TFE / CTFE / PPVE (molar ratio): 76.3 / 21.3 / 2.4 Melting point: 245℃ MFR: 3g / 10min (297℃, 5kg)
[0106] Comparative Example 1 Pellets of the copolymer (a1) and a tube manufacturing apparatus were used to manufacture 1 / 2 inch tubes having an outer diameter of 12.70 mm and a thickness of 1.58 mm.
[0107] Comparative Example 2 A 1 / 2 inch tube was produced in the same manner as in Comparative Example 1, except that the copolymer (a2) was used instead of the copolymer (a1).
[0108] Comparative Example 3 Using a two-kind, two-layer tube extrusion device equipped with a multi-manifold, the inner layer (A) was copolymer (a1) and the outer layer (B) was polymer (b1), and the two extruders were fed to each extruder to produce a 1 / 2-inch tube having an outer diameter of 12.70 mm and a thickness of 1.58 mm. The thickness of the inner layer (A) was 1.05 mm, and the thickness of the outer layer (B) was 0.53 mm.
[0109] Example 1 A 1 / 2 inch tube was produced in the same manner as in Comparative Example 3, except that the copolymer (a2) was used instead of the copolymer (a1).
[0110] (Tube evaluation) 35% by mass hydrochloric acid was sealed in the tubes produced in Comparative Examples 1 and 2 and Example 1, and the tubes were left in 80° C. warm water for 90 hours. The tubes were removed from the warm water, and the cross sections of the tubes were observed using a digital microscope. Images of the cross sections of the tubes are shown in FIGS. 1 to 3.
[0111] The cross-sectional image of the tube shown in Figure 3 shows that the tube having an inner layer formed from the copolymer (a) with an appropriately adjusted weight loss rate has no cracks in the inner layer, whereas the cross-sectional images of the tube shown in Figures 1 and 2 show that the single-layer tube has numerous cracks with lengths of 10 μm or more.
[0112] (Measurement of 35% hydrochloric acid permeability coefficient) As shown in FIG. 4, one end of the tubes prepared in Comparative Example 3 and Example 1 was heat-sealed, 52 ml of 35% by mass hydrochloric acid was placed in the tube 21, and the other end of the tube was also heat-sealed. The tube 21 containing hydrochloric acid was inserted into a glass tube 22 and fixed using a fluororubber packing 23. Next, 110 ml of pure water was charged from the sampling port 24 and placed in a thermostatic chamber at 25°C. At this time, the tube between the packings 23 was in contact with the pure water, and the length of the liquid-contacting portion was 18.5 cm. After leaving it in this state, about 1 ml was sampled from the sampling port 24, and the chloride ion concentration Y (ppm) contained in the pure water was quantified using an ion chromatograph (product name: IC7000-E, manufactured by Yokogawa Electric Corporation), and the hydrochloric acid permeability coefficient (X) (ng·cm / cm 2 / days) was calculated. Formula: X = [(β × film thickness) / cross-sectional area] / (8.64 × 10 7 ) β (unit: μg / sec): The slope of the tangent to the permeation curve for 150 to 250 days (T=150 to 250) drawn by plotting α against T. α: Total amount of transmitted light (unit: μg) = Y × W Y: Chloride ion concentration (unit: ppm) W: Pure water volume (unit: ml) T: Time elapsed from the start of permeation (the point at which hydrochloric acid was poured into the double-layer tube) to sampling (unit: seconds) Film thickness: Tube wall thickness (unit: cm, 1.58 mm (0.158 cm)) Cross-sectional area: The area of the part where the double-walled tube and the pure water are in contact with each other in the experimental apparatus shown in Figure 4 (unit: cm 2 )
[0113] The 35% hydrochloric acid permeability coefficients (for 150 to 250 days) of the tubes produced in Comparative Example 3 and Example 1 were as follows. Comparative example 3: 20ng·cm / cm 2 / days Example 1: 7ng cm / cm 2 / days
Claims
1. A two-layer tube comprising an inner layer (A) and an outer layer (B) provided directly on the inner layer (A), the inner layer (A) contains a copolymer (a) containing tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, The outer layer (B) contains a polymer (b) containing at least a chlorotrifluoroethylene unit, The weight loss rate of the copolymer (a) after heat treatment at 380° C. for 1 hour is 0.05% by mass or less, The ratio ((A) / (B)) of the thickness of the inner layer (A) to the thickness of the outer layer (B) is 30.0 / 70.0 to 67.0 / 33.
0. Double layer tube.
2. 2. The double-layer tube according to claim 1, wherein the total thickness of the inner layer (A) and the outer layer (B) is 1.3 mm or more.
3. 3. The double-layer tube according to claim 1, wherein the total thickness of the inner layer (A) and the outer layer (B) is 1.56 to 1.64 mm.
4. 3. The double-layer tube according to claim 1 or 2, wherein the content of perfluoro(propyl vinyl ether) units in the copolymer (a) is 4.0 to 6.5 mass% based on the total monomer units constituting the copolymer (a).
5. 3. The double-layer tube according to claim 1, wherein the melting point of the copolymer (a) is 295 to 308°C.
6. 3. The double-layer tube according to claim 1, wherein the polymer (b) is a copolymer containing chlorotrifluoroethylene units, tetrafluoroethylene units and monomer (α) units derived from a monomer (α) copolymerizable therewith.
7. 3. The double-layer tube according to claim 1, wherein the polymer (b) is a copolymer containing chlorotrifluoroethylene units, tetrafluoroethylene units and perfluoro(alkyl vinyl ether) units.
8. The zero shear viscosity of the copolymer (a) is 2.00×10 4 3. The double-layer tube according to claim 1, having a viscosity of at least Pa·S.
9. 3. The double-layer tube according to claim 1, wherein the copolymer (a) has an MIT value of 2.6 million or more.
10. 3. The double-wall tube according to claim 1, wherein no cracks having a length of 10 μm or more are present in the inner layer (A) after sealing an acid aqueous solution containing at least one acid selected from the group consisting of hydrochloric acid, hydrofluoric acid, nitric acid, and sulfuric acid and leaving it at room temperature for 150 days or more.
11. 3. The double-layer tube according to claim 1, wherein the inner layer (A) is free of cracks having a length of 10 μm or more after the tube is filled with 35% by mass hydrochloric acid and left in warm water at 80° C. for 90 hours.
12. The copolymer (a) may contain other monomer units derived from monomers copolymerizable with tetrafluoroethylene and perfluoro(propyl vinyl ether), the content of perfluoro(propyl vinyl ether) units in the copolymer (a) is 4.0 to 6.5 mass% based on all monomer units constituting the copolymer (a), the content of tetrafluoroethylene units in the copolymer (a) is 93.5 to 96.0 mass% based on all monomer units constituting the copolymer (a), and the content of other monomer units in the copolymer (a) is 0 to 1.5 mass% based on all monomer units constituting the copolymer (a); Polymer (b) is a copolymer containing chlorotrifluoroethylene units, tetrafluoroethylene units and perfluoro(alkyl vinyl ether) units, and the content ratio of each monomer (chlorotrifluoroethylene units / tetrafluoroethylene units / perfluoro(alkyl vinyl ether) units (mol %)) is (15.0 to 24.9) / (75.0 to 84.9) / (0.1 to 10.0); The total thickness of the inner layer (A) and the outer layer (B) is 1.56 to 1.64 mm; The ratio ((A) / (B)) of the thickness of the inner layer (A) to the thickness of the outer layer (B) is 60.0 / 40.0 to 67.0 / 33.
0. The double-layer tube according to claim 1 or 2.
13. A method for producing the double-layer tube according to claim 1 or 2, comprising the steps of: A manufacturing method in which copolymer (a) is subjected to a heat treatment by blowing hot air at 200 to 280°C for 6 hours or more, and then the resulting copolymer (a) and polymer (b) are laminated to obtain a two-layer tube.
Citation Information
Patent Citations
Heat fixing member and image forming apparatus having the same
JP2004163715A
Fluororesin molding
JP2017119750A
Copolymer, injection molding, compression member and covered wire
JP2022058292A
Fluid transferring tube, semiconductor manufacturing line system and liquid crystal panel manufacturing line system
WO2005047747A1
Chlorotrifluoroethylene copolymer
WO2005100420A1
